Pengembangan Media Permainan Puzzle pada Siswa SMP dengan Materi Teks Eksposisi - Yusati Adil Hulu; Ya’aman Gulo; Thantri Ayu Telaumbanua; Mastawati Druru (Journal on Education, 2023)
This research is to describe the suitability of puzzle media as a learning tool on expository text material and to find out students' reactions to the use of puzzle media on expository text material. The method used is research and development (R&D), a product manufacturing research method. The questionnaire method was used as a research data collection method in this study, where research results were collected and students' responses to the media used were evaluated. Based on the research results, it is known that 87.40% of respondents stated that the puzzle environment is very useful as a learning tool. Two students gave a very strong reaction to the puzzle media in the exhibition text material as a result of the exhibition results. Distribution of questionnaires to students.